Intervertebral Disc Degeneration in Long-Term Postoperative Patients with Adolescent Idiopathic Scoliosis: MRI Evaluation 34-51 Years after Surgery and its Changes during Middle and Older Age for an Average of 6.9 Years - Tsutomu Akazawa; Toshiaki Kotani; Tsuyoshi Sakuma; Yasushi Iijima; Yoshiaki Torii; Jun Ueno; Atsuhiro Yoshida; Ken Tomochika; Sumihisa Orita; Yawara Eguchi; Kazuhide Inage; Yasuhiro Shiga; et al. (Spine Surgery and Related Research)
Introduction: This study aimed to identify factors associated with intervertebral disc degeneration (DD) in adolescent idiopathic scoliosis (AIS) patients who reached middle and older age after surgery. Methods: A total of 252 AIS patients who underwent spinal fusion surgery between 1968 and 1988 were included in this survey-based study. Patients with a mean follow-up period of 40.9 years were evaluated through lumbar spine magnetic resonance imaging (MRI), radiographic assessments, and patient-reported outcome measures (PROMs). DD was evaluated using the Pfirrmann grading system. Various factors, such as surgical levels, sagittal alignment, and PROMs, were analyzed for their association with DD. Results: Among the 21 participants who underwent both previous (conducted from 2014 to 2016) and latest surveys (conducted in 2022), the prevalence of DD increased from 66.7% in the previous survey to 76.9% in the latest survey. The overall Pfirrmann disc score significantly increased from 3.2 to 3.5. Sagittal alignment parameters, such as sagittal vertical axis (SVA), pelvic incidence minus lumbar lordosis (PI-LL), and pelvic tilt (PT), worsened over time. Scores in the Scoliosis Research Society-22 Questionnaire pain, Roland-Morris Disability Questionnaire, and Oswestry Disability Index were significantly worse in the latest survey than in the previous one. Comparison between patients with the lower instrumented vertebra (LIV) at L4 or lower and L3 or higher revealed significantly higher disc scores and 100% prevalence of DD in the L4 or lower group. Factors associated with DD included LIV at L4 or lower, smaller LL, larger thoracolumbar kyphosis, and increased SVA, PI-LL, and PT. Conclusions: This study suggests that maintaining the LIV at L3 or higher, achieving good sagittal alignment, and maintaining LL may help prevent long-term DD in AIS patients.